The use of adenoviral vectors in gene therapy and vaccine approaches - Natália Meneses Araújo; Ileana Gabriela Sanchez Rubio; Nicholas Pietro Agulha Toneto; Mirian Galliote Morale; Rodrigo Esaki Tamura (Genetics and Molecular Biology, 2022)
Abstract Adenovirus was first identified in the 1950s and since then this pathogenic group of viruses has been explored and transformed into a genetic transfer vehicle. Modification or deletion of few genes are necessary to transform it into a conditionally or non-replicative vector, creating a versatile tool capable of transducing different tissues and inducing high levels of transgene expression. In the early years of vector development, the application in monogenic diseases faced several hurdles, including short-term gene expression and even a fatality. On the other hand, an adenoviral delivery strategy for treatment of cancer was the first approved gene therapy product. There is an increasing interest in expressing transgenes with therapeutic potential targeting the cancer hallmarks, inhibiting metastasis, inducing cancer cell death or modulating the immune system to attack the tumor cells. Replicative adenovirus as vaccines may be even older and date to a few years of its discovery, application of non-replicative adenovirus for vaccination against different microorganisms has been investigated, but only recently, it demonstrated its full potential being one of the leading vaccination tools for COVID-19. This is not a new vector nor a new technology, but the result of decades of careful and intense work in this field.